GENDER QUOTAS, FRAUD AND FEMALE REPRESENTATION: THE CHALLENGES OF THE BRAZILIAN MODEL AND THE WAYS TO ITS IMPROVEMENT - Travincas, Amanda Costa Thomé; Lula, Carlos Eduardo de Oliveira (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
This article examines the effectiveness of gender quotas in Brazil, identifying distortions such as fraudulent female candidates ("laranjas") and their impact on political representation. The study was conducted using documentary analysis and comparative jurisprudence, examining decisions of the Superior Electoral Court (TSE) and Brazilian electoral legislation from 1988 to 2024. Emblematic cases of fictitious candidacies were selected to compare structural patterns of implementation and penalties. A scientific legal framework was used, with qualitative interpretative analysis and comparison of institutional models of international political electoral systems, particularly Mexico. The results reveal that, despite the legislative requirement of 30% female candidates, female representation in Parliament remained low, exacerbated by integrated impeachments that affected legitimate candidates, generating paradoxical effects. In contrast, a country like Mexico, through closed lists and reserved seats, achieved almost 50% female representation. It is concluded that Brazil must move towards quotas with guaranteed results, strengthening institutional effectiveness, preventing fraud and aligning itself with international best practices within the constitutional principles of political equality.